(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the potential for unlocking green investment opportunities in Uzbekistan through the implementation of household-scale solar panels. Meeting the energy needs of the population via sustainable and environmentally friendly sources not only strengthens economic independence but also contributes to environmental stability. The research thoroughly examines the economic efficiency of micro-level investments, the rational use of resources, the achievement of reduced electricity costs, and the prospects for scaling this model across households. Based on a SWOT analysis, existing opportunities and constraints are identified, framing this approach as a practical tool for Uzbekistan’s long-term green development path.